The Effect of E-Money on the Money Supply and Inflation di Indonesia Year 2019-2021 - Mulyani, Yani; Davronov, Istamkhuja Olimovich (Yayasan Sinergi Kawula Muda, 2023)
This study aims to examine the results of data on the effect of e-money on the money supply and inflation in Indonesia in 2019-2021. In this study, researchers used a quantitative approach. The data used in this study are secondary data. Sample determination is carried out by purposive sampling method. The data processing technique used is a multiple linear regression method using the eviews application. The results of this study show that E-money has a significant positive effect on the variables of Money Supply and Inflation, and the Money Supply has a significant positive effect on the variable Inflation.